2015
DOI: 10.1186/s12889-015-2653-x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory analyses of virologic outcomes reflecting community-based HIV treatment in Washington DC 1994–2012

Abstract: BackgroundEffective treatment of HIV since 1996 has reduced morbidity and mortality through virologic suppression. Combination antiretroviral therapy (cART) has been recognized as key to the prevention of drug resistance and the transmission of infection. We used eighteen years of virologic outcomes in a long-standing cohort of women to describe longitudinal viral load trajectories; and examine factors associated with sustained viremia and mortality.MethodsWe analyzed data from DC WIHS women with > four semian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…This study offers insight into the dynamic and heterogeneous nature of the longitudinal VL trajectories of WLWH, not captured by cross-sectional study designs. 22 We identified three distinct group-based VL trajectory patterns, comparable in number and shape to those described in Ocampo et al.’s 2015 study 20 : (1) ‘ sustained low probability of detectable VL’ (similar to Ocampo’s ‘non-viremia’ trajectory 20 ) ; (2) ‘ high probability of delayed viral undetectability’ (comparable to Ocampo’s ‘intermittent viremia’ trajectory 20 ); and (3) ‘ high the probability of detectable VL’ (similar to Ocampo’s ‘viremia’ trajectory 20 ) . We also found that lifetime incarceration, younger age at baseline, and lower baseline CD4 levels predicted a ‘ high probability of delayed viral undetectability’ compared to a ‘ sustained low probability of detectable VL’ .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This study offers insight into the dynamic and heterogeneous nature of the longitudinal VL trajectories of WLWH, not captured by cross-sectional study designs. 22 We identified three distinct group-based VL trajectory patterns, comparable in number and shape to those described in Ocampo et al.’s 2015 study 20 : (1) ‘ sustained low probability of detectable VL’ (similar to Ocampo’s ‘non-viremia’ trajectory 20 ) ; (2) ‘ high probability of delayed viral undetectability’ (comparable to Ocampo’s ‘intermittent viremia’ trajectory 20 ); and (3) ‘ high the probability of detectable VL’ (similar to Ocampo’s ‘viremia’ trajectory 20 ) . We also found that lifetime incarceration, younger age at baseline, and lower baseline CD4 levels predicted a ‘ high probability of delayed viral undetectability’ compared to a ‘ sustained low probability of detectable VL’ .…”
Section: Discussionsupporting
confidence: 64%
“…While we hypothesized that there would be three VL trajectory groups, 20 we tested for the possibility of between 2-6 latent trajectory groups. Up to a cubic polynomial function was considered for each group to allow for maximum flexibility in trajectory forms, and backward selection of time-related parameters (e.g., linear, quadratic, cubic) was employed, based on statistical significance (at p ≤0.10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of this phenomenon mirrors previous findings among the Washington, DC, WIHS participants. 12 This phenomenon supports the need for regionally representative viral load and drug resistance surveillance. Conversely, analysis of our most recent data demonstrates that women without previous viral suppression can achieve and maintain viral suppression.…”
Section: Discussionmentioning
confidence: 61%
“… 12 Using a group-based trajectory analysis we identified 3 distinct longitudinal viremia trajectory patterns: high, intermediate, and low probability of viral suppression. 12 This initial study was limited to the mid-Atlantic WIHS participants. We expanded this analysis to the national WIHS cohort that has representation from across the United States to determine whether similar longitudinal patterns of viremia emerge.…”
Section: Introductionmentioning
confidence: 99%